Experiment to find the neutron clusters in the decay of 238U nuclei; Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment; Vol. 834 - Bystritsky V. M. Vyacheslav Mikhaylovich; Dudkin G. N. Gennadiy Nikolaevich; Kuznetsov S. I. Sergey Ivanovich; Varlachev V. A. Valery Aleksandrovich; Padalko V. N. Vladimir Nikolaevich (2016, 2016)
Title screen